Biomarkers for diagnosis, disease progression, and therapeutic response in psoriasis vulgaris: A mini-review - Edwar, Sarah Q.; Irawan, Yudo; Budianti, Windy K.; Novianto, Endi; Fitri, Eyleny M. (Narra J, 2026)
Psoriasis vulgaris is a chronic immune-mediated inflammatory disease with substantial clinical, psychosocial, and public health impact. Despite advances in therapeutic options, disease management continues to rely predominantly on clinical assessment, which remains limited in its ability to detect early disease, quantify subclinical inflammation, monitor disease progression, and anticipate long-term outcomes. These limitations are further compounded by marked interindividual heterogeneity in disease course, systemic inflammatory burden, comorbidity risk, and treatment response. Although a growing body of research has identified numerous candidate biomarkers related to genetic susceptibility, epidermal pathology, immune activation, and systemic inflammation, their clinical relevance and integration into routine practice remain unclear. A comprehensive synthesis that bridges molecular biomarkers with clinically meaningful applications is therefore needed. This review critically examines the current landscape of biomarkers in psoriasis vulgaris and explores their potential roles in diagnosis, assessment of disease progression, and prediction of therapeutic response. This review discusses genetic biomarkers associated with disease susceptibility and immune pathway regulation, tissue-associated biomarkers reflecting epidermal dysfunction and local inflammatory activity, and soluble biomarkers indicative of systemic inflammation and metabolic dysregulation. By organizing existing evidence across these biomarker domains, this review seeks to highlight conceptual frameworks, unresolved challenges, and future directions for biomarker-informed psoriasis management.